Service user and carer involvement in online interprofessional learning during the COVID-19 pandemic. (2nd February 2023) - Coleman, Tracy; Bennett-Weston, Amber; Sy, Michael; Greaves, Jane; Anderson, Elizabeth S
Abstract : Patients, service users and carers are now expected to contribute to teaching health and social care students in all professions. This follows policy directives driven by a review of failings in NHS standards for patient involvement in all aspects of health and social care. Patient and carer contributions to interprofessional education hold fast to values for patient/carer-centred care. This article discusses the context to service user and carer involvement in health professions education, drawing on current evidence and with considerations for midwifery students. A case study of a well-established carer's session is presented, drawing on the input of a mother, which was continued online during the pandemic. It was ensured that this important learning was not lost when teaching became remote, relying on technology-enhanced learning methods. These adaptations depend on long-standing patient partnerships between faculty in higher education institutions and patients/carers who must feel safe and trust the teaching context where they contribute to student learning. Effective learning can be maintained in online environments to ensure the patient voice remains central to health professions training.